2015
DOI: 10.1007/s13277-015-3397-z
|View full text |Cite
|
Sign up to set email alerts
|

Mdig, a lung cancer-associated gene, regulates cell cycle progression through p27KIP1

Abstract: Mineral dust-induced gene (mdig) can accelerate cell proliferation. The aim of this study is to investigate the mechanism by which mdig regulates cell proliferation. A549 cells were transfected with siRNA specifically targeting mdig. Cell proliferation and cell cycle progression were measured using MTT assay and cell cycle analysis, respectively. Furthermore, real-time reverse transcription quantitative-polymerase chain reaction (RT-qPCR) was performed in A549 cells transfected with mdig siRNA to examine the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Multiple oncogenic factors including Skp2 [197] and Mdig [198] inhibiting p27 activation by accelerating its degradation, leading to higher cytoplasmic p27 expression, indicating poorer chemosensitivity and long-term survival among patients of non-small cell lung cancer [199]. Similarly, repressed p27 viability is likewisely identified as an inevitable pusher of neoplastic transformation in prostate.…”
Section: Functions Of Ampk Signaling Components In Tumorigenesismentioning
confidence: 99%
“…Multiple oncogenic factors including Skp2 [197] and Mdig [198] inhibiting p27 activation by accelerating its degradation, leading to higher cytoplasmic p27 expression, indicating poorer chemosensitivity and long-term survival among patients of non-small cell lung cancer [199]. Similarly, repressed p27 viability is likewisely identified as an inevitable pusher of neoplastic transformation in prostate.…”
Section: Functions Of Ampk Signaling Components In Tumorigenesismentioning
confidence: 99%
“…It has been found that silencing Mdig/mina53 mRNA expression in A549 lung cancer cells suppresses cell proliferation by delaying the cell cycle transition from G1 to S phase (4,18). These results indicate that Mdig/mina53 might promote cell proliferation by regulating the G1/S transition.…”
Section: Regulation Of Cell Cycle and Cell Proliferationmentioning
confidence: 87%
“…Furthermore, the phosphorylation of p27 KIP1 at its Thr187 site was also inhibited. Importantly, Ma et al (18) also found that upregulation of Mdig/mina53 was accompanied by downregulation of p27 KIP1 in both lung cancer tissues and bronchial stump. This suggests that Mdig/mina53 play an essential role in the cell cycle regulation, cell proliferation and tumor formation by inhibiting p27 KIP1 expression through the phosphorylation of its Thr187 site.…”
Section: Regulation Of Cell Cycle and Cell Proliferationmentioning
confidence: 93%
See 1 more Smart Citation
“…Many substances can induce mdig expression, such as arsenic (2) and mineral dust (3), among others. It has been reported that mdig is a proto-oncogene that is highly expressed in a variety of tumor cells, where it not only serves as an independent factor leading to tumor formation, but also as a promoter of tumor cell proliferation (1,(4)(5)(6). Mdig/mina53 is a downstream target gene of the transcription factor c-Myc, and is located on chromosome 3 (3q12.1).…”
Section: Introductionmentioning
confidence: 99%